2009
DOI: 10.1097/qco.0b013e328320a85d
|View full text |Cite
|
Sign up to set email alerts
|

Sexually transmitted diseases and incarceration

Abstract: The clinical tools are available to improve STD prevention, screening, and treatment in correctional facilities. However, more research and advocacy is needed to convince decision makers of the importance of committing the necessary resources and adopting the policies needed to close the gap between opportunity and reality in correctional STD programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
24
0
2

Year Published

2010
2010
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 23 publications
2
24
0
2
Order By: Relevance
“…These findings are consistent with the results of previous studies of incarcerated women Willers et al, 2008). A review of the literature on STDs within adult and juvenile correctional institutions by Hammett (2009) summarizes numerous studies that report that a larger percentage of women than men in these facilities have an STD. Previous research has also shown that having an STD history puts an individual at a much greater risk for contracting human immunodeficiency virus (HIV; Willers et al, 2008; Wasserheit, 1992;Westrom, Joesoef, & Reynolds, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…These findings are consistent with the results of previous studies of incarcerated women Willers et al, 2008). A review of the literature on STDs within adult and juvenile correctional institutions by Hammett (2009) summarizes numerous studies that report that a larger percentage of women than men in these facilities have an STD. Previous research has also shown that having an STD history puts an individual at a much greater risk for contracting human immunodeficiency virus (HIV; Willers et al, 2008; Wasserheit, 1992;Westrom, Joesoef, & Reynolds, 1992).…”
Section: Discussionsupporting
confidence: 92%
“…It has been reported that few systems in the United States have adopted condom provision for inmates, in the face of evidence that high-risk sexual behaviors occur in correctional settings. 30 High levels of opioid use, high proportion of IDUs, as well as existing shared drug injection among prisoners in this custodial setting underscore the need to introduce opioid-substitute treatment, such as MMT. Thus, the introduction of the MMT program for opioid-dependent prisoners in this prison is an important and welcomed effort by the Iran Prison Organization to tackle opioid-related harm among prisoners.…”
Section: Discussionmentioning
confidence: 99%
“…As an example, only 4% of the jail systems in the United States provide mandatory or routine STI screenings (Hammett, 2009). Douglas County Department of Corrections (DCDC), a jail facility housing an average daily population of about 1,500 inmates, serves a population of about 1 million people in the Omaha metropolitan area in Nebraska and currently does not provide routine STI testing.…”
Section: Introductionmentioning
confidence: 99%